Needs and Wants Theory: A comparison between Maslow’s Hierarchy of Needs and Maqasid al Shariah - Abdul Razak, Dzuljastri; Ab. Hamid, Siti Ngayesah; Ya'kob, Siti Aisyah (2013)
Maslow's hierarchy of needs can be categorized under five levels namely physiological, safety, social, self-esteem and self-actualization. In contrast, needs level under Maqasid al-Shariah are categorized under three levels namely essentials (daruriyyah), complementary (hajiyyah) and embellishment (tahsiniyyah). This paper attempts to compare the differences between the conventional and Islamic need theories towards satisfaction of human needs and wants. The observations indicate both Maslow and Maqasid al-Shariah are able to fulfill human needs and wants. However, the achievement by the former is materially driven as there seems to be no limit to the fulfillment of human wants. Whereas the later, takes into consideration justice, spiritual dimension and the concern for public interest (maslahah).